Technology in Arabic Language Learning - Faidatul Baroro (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
This study explores the crucial role of technology in learning the Arabic language, emphasizing its importance in today's digital landscape and the challenges faced during its implementation. In this context, "technology" refers to a diverse array of digital tools and resources, including mobile applications, e-learning platforms, interactive multimedia, and artificial intelligence (AI), all aimed at enhancing the Arabic learning experience. Research has demonstrated that integrating technology can boost learner motivation, expand access to educational materials, encourage self-directed learning, and foster interaction with native speakers. The application of technology in Arabic language education has evolved from basic audiovisual aids to sophisticated digital systems. Nonetheless, several challenges remain, such as inadequate infrastructure, low levels of digital literacy, and the intrinsic complexities of the Arabic language. This study employs a library research methodology, analyzing a variety of academic literature to derive meaningful insights. The findings are intended to guide educators and developers of Arabic language learning technologies in overcoming the hurdles of education in the digital era.